Current predation risk has opposing effects on social learning of foraging locations across two guppy populations - Mélanie F. Guigueno; Adrian C. K. Foster; Simon M. Reader (Animal Cognition)
Abstract Social learning, where animals learn from other individuals, occurs in many diverse species. The influential but debated ‘costly information’ hypothesis posits that animals will rely more on social information in high-risk contexts, such as under increased predation risk. We examined and compared the effects of perceived predation risk on social learning of foraging sites in female Trinidadian guppies from wild and domestic populations raised in common-garden environments. We used a demonstrator-observer pairing where a subject could observe conspecific ‘demonstrators’ feeding from one of two feeders, and measured whether the observer subsequently spent more time at a demonstrated or non-demonstrated feeder. We manipulated perceived predation risk using alarm cue (conspecific skin extract). Stress responses and social learning differed between the two populations. Most notably, high predation risk enhanced social learning in the wild-type guppies, but depressed it in the domestic guppies. Thus, fish from both populations were able to socially learn, but under opposing contexts. These results suggest social learning propensities are the product of multiple interacting systems, and biases to favour social learning can emerge dependent on evolutionary history and current conditions.